Fullerenes : principles and applications - Langa, Fernando; Nierengarten, Jean-Francois (Royal Society of Chemistry, 2007)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.
Keywords: Fullerenes.; Carbon.; Nanotubes.; Fullerenes -- Industrial applications.; elektronické knihy; electronic books